TOLERANSI BERAGAMA DALAM AL-QUR’AN MENURUT SYAIKH NAWAWI AL-BANTANI - Ahmad Ma’rup (Reflektika, 2018)
This paper explains the ethics of the Qur'an towards non-Muslims. Islam as a religion of peace is often accused and harassed by the haters of Islam. The accusations and harassment were contained in several articles, journals, and books. In fact, Islam is not as alleged by them. Even Islam retaliated against these accusations with very tolerant teachings. Islam teaches its followers to respect people of other religions, forbids them from insulting other religions, criticizing their worshipers, or forcing non-Muslims to embrace Islam, even Islam teaches its followers to recognize non-Muslims as brothers. This is Islam's respect for non-Muslims. So in this case, one of the figures who is firm is Shaykh Nawawi al-Bantani, who offers good and right religious tolerance. Shaykh Nawawi al-Bantani was born in 1230 H or 1815 AD. However, there are those who state that Shaykh Nawawi was born in 1814 AD and died in Mecca on 25 Shawwal 1340 AD / 1897 AD. In this journal the author describes the nature of religious tolerance and its limitations and in this journal using the method of interpretation and description by using the type of research library research with descriptive analysis.